Supervisory control synthesis for large-scale systems with isomorphisms. (October 2021) - Moormann, L.; van de Mortel-Fronczak, J.M.; Fokkink, W.J.; Maessen, P.; Rooda, J.E.
Abstract: The complexity of the design of supervisory controllers for today's high-tech systems is ever increasing with the rise in demands for higher safety and functionality. Supervisory control synthesis enables the design engineer to automatically generate a supervisory controller from a model of the plant and a model of the controller requirements. Although supervisory control theory is an active research area, the number of industrial applications remains relatively low. One of the main reasons for this is the lack of guidelines for practical applications of supervisory control theory, especially in case of large-scale systems with numerous components and complex dependencies. In this paper, guidelines are given for the process of obtaining and validating a supervisory controller, more specifically for large-scale systems with isomorphisms. Systems with isomorphisms are systems with a high degree of symmetry and repetitiveness in their components, such as manufacturing lines with parallel processing lines or infrastructural systems with repeating modules. This paper shows how coordination between the steps in obtaining a supervisory controller for a large-scale system improves the efficiency of the process and quality of the end result, and how the isomorphism of components in the system can be exploited in these steps. This process is demonstrated in this paper by a case study related to the Eerste Heinenoordtunnel, a road tunnel in the Netherlands. The case study shows the steps of modeling the plant and the controller requirements, performing model reduction based on isomorphisms in the system, synthesizing the supervisory controller, and validating the controller by means of simulation. Highlights: A supervisor for a road tunnel is synthesized with 10 257 states. Parameter-based modeling is introduced as an accessible modeling method. The model is reduced using isomorphisms decreasing the synthesis time by a factor 210. The synthesized supervisor is validated by means of visualized simulations.